Status Padang Lamun Pantai-Pantai Wisata di Pacitan - Nurul Kusuma Dewi; Sigit Ari Prabowo (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
The purpose of this research was to study the condition of seagrass communities at Pacitan coast. The study was conducted at Klayar, Srau, Teleng Ria, Pancer, Tawang, and Pidakan at Pacitan coast. The presence of seagrass communities was determined by the physical and chemical factors. Data were collected using quadrate plots with five transects. At each transect, data was collected using the quadrate plot, 0.5 m x 0.5 m, with 11 replications. On each plot, number of species, density, and their coverage were measured. Water quality such as light penetration, water level, current velocity, salinity, temperature, wave height, DO, pH, sediment texture, and nutrients of NH4, NO3, PO4, C-organic were also measured. The results showed, from 6 beaches studied, seagrass is only found in Tawang and Pidakan. There were 3 species of seagrass in Tawang beach, i. e Cymodocea serrulata, Thalassia hemprichii, and Halophila ovalis which were distributed unevenly, with 37,66 % coverage. In Pidakan beach, there is 1 species of seagrass, Thalassia hemprichii, with 30,89 % coverage. These variations were due to the physical and chemical factors in each location. T. hemprichii was the seagrass species which was tolerant to changes in environmental conditions. Light and substrate were as important factors that determined the presence and abundance of seagrass communities in Pacitan coastal waters.Keywords: coverage, light, seagrass, substrate, tolerant species